Custard's last stand a Pennsylvania Dutch mystery with recipes - Myers, Tamar (New York : Signet Book, 2004)
When Colonel George Custard, the hotel tycoon who had selected her hometown of Hernia, Pennsylvania, as the site for his new five-star hotel, despite much local opposition, turns up dead, innkeeper and amateur sleuth Magdalena Yoder searches for a killer.
89246
Keywords: Yoder, Magdalena (Fictitious character) -- Fiction; Women detectives -- Pennsylvania -- Fiction; Hotelkeepers -- Fiction; Mennonites -- Fiction; Cookery -- Pennsylvania; Pennsylvania Dutch Country (Pa.) -- Fiction; Pennsylvania -- Fiction; Mystery fiction